The Effect of the Widuri Program on High School Students' Knowledge about Bung Hatta at the UPT Proklamator Bung Hatta Library - Aprilina, Sierly Ananta; Rahmah, Elva (Darul Yasin Al Sys, 2026)
The limited and often superficial understanding of national figures among students, particularly Bung Hatta, reflects a critical gap between the intended objectives of history education and actual learning outcomes, which remain largely focused on memorization rather than deep conceptual understanding. This issue is closely associated with conventional, teacher-centered instructional approaches that provide limited contextualization and experiential engagement. This study aims to empirically examine the effect of the WIDURI Program, a library-based educational initiative grounded in experiential learning, on high school students’ knowledge of Bung Hatta. A quantitative explanatory design was employed, involving 70 respondents selected through simple random sampling. Data were collected using a validated and reliable Likert-scale questionnaire and analyzed through simple linear regression after meeting classical assumption requirements. The findings indicate that the WIDURI Program has a positive and statistically significant effect on students’ knowledge, as shown by a significance value of 0.000 (< 0.05) and a regression coefficient of 0.729. The coefficient of determination (R² = 0.277) further indicates that the program contributes 27.7% to the variance in students’ knowledge. These findings demonstrate that experiential learning within a library context can enhance students’ factual knowledge while also supporting higher-order cognitive skills in line with Bloom’s Taxonomy. This study contributes to history education and library-based learning literature by highlighting the transformative role of libraries as active learning environments rather than passive information providers. Practically, the findings imply that experience-based literacy programs can serve as strategic and innovative approaches to fostering more contextual, critical, and meaningful learning outcomes.